2021
DOI: 10.3390/informatics8040072
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Contact Tracing and Detection-Based on Blockchain Technology

Abstract: The fight against the COVID-19 pandemic still involves many struggles and challenges. The greatest challenge that most governments are currently facing is the lack of a precise, accurate, and automated mechanism for detecting and tracking new COVID-19 cases. In response to this challenge, this study proposes the first blockchain-based system, called the COVID-19 contact tracing system (CCTS), to verify, track, and detect new cases of COVID-19. The proposed system consists of four integrated components: an infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For instance, blockchain technology has been proposed to preserve privacy during contact tracing for COVID-19 pandemic to gain trust by users [25][26] [27]. According to [26], it was reported that blockchain technology was able to detect unknown cases of COVID-19. The application was also capable of enabling individuals to use the mobile application to predict the probabilities of being infected.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, blockchain technology has been proposed to preserve privacy during contact tracing for COVID-19 pandemic to gain trust by users [25][26] [27]. According to [26], it was reported that blockchain technology was able to detect unknown cases of COVID-19. The application was also capable of enabling individuals to use the mobile application to predict the probabilities of being infected.…”
Section: Related Workmentioning
confidence: 99%
“…Contact tracing requires people to share their private contact history, sometimes even including sensitive information such as GPS coordinates or medical history [202,203] . Most initial attempts of blockchain-powered contact tracing approaches are of high level and treat blockchain naively as external storage or with no simulation provided to illustrate the effectiveness, such as BeepTrace [204] , Arifeen et al [205] , and Choudhury et al [206] Hasan et al [207] proposed to use blockchain to record participants' GPS coordinates and trigger proof of location to conduct contact tracing and risk alert. In their proposed system, external oracles are adopted to conduct contact tracing algorithm, and blockchain works as a bridge from external oracles to involved parties, including testing center and patients.…”
Section: Blockchain-enabled Contact Tracingmentioning
confidence: 99%
“…Although the implementation demonstrates the feasibility of the proposed approach, the use of zero-knowledge scheme could determine high drain of battery in a real life scenario. In [23] an integrated contact tracing system is proposed to verify, track, and detect new cases of COVID-19. The proposed system consists of three components: an infection verifier subsystem, a mass surveillance subsystem and a P2P mobile plus a blockchain employed for managing all transactions between the three subsystems.…”
Section: Related Workmentioning
confidence: 99%